2014
DOI: 10.15326/jcopdf.2.1.2014.0148
|View full text |Cite
|
Sign up to set email alerts
|

National COPD Readmissions Summit 2013: Integrating COPD into Patient-Centered Hospital Readmissions Reduction Programs

Abstract: About 1 in 5 patients hospitalized for exacerbations of chronic obstructive pulmonary disease (COPD) in the United States are readmitted within 30 days. The U.S. Centers for Medicare and Medicaid Services has recently expanded its Hospital Readmissions Reduction Program to financially penalize hospitals with higher than expected all-cause 30-day readmission rates following a hospitalization for COPD exacerbation. In October 2013, the COPD Foundation convened a multi-stakeholder National COPD Readmissions Summi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…4 As a result of this financial incentive, hospitals across geographic regions have been implementing programmes directed at reducing readmissions among patients with COPD. 25 Likely as a result of this, Medicare data has shown that readmission rates among COPD patients have declined markedly since 2012. 26 While studies prior to 2012 showed a positive association between pulmonary disease and readmission risk, 6,19 we believe these CMS incentives underlie the reduced risk of readmission we observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 As a result of this financial incentive, hospitals across geographic regions have been implementing programmes directed at reducing readmissions among patients with COPD. 25 Likely as a result of this, Medicare data has shown that readmission rates among COPD patients have declined markedly since 2012. 26 While studies prior to 2012 showed a positive association between pulmonary disease and readmission risk, 6,19 we believe these CMS incentives underlie the reduced risk of readmission we observed.…”
Section: Resultsmentioning
confidence: 99%
“…During the period of analysis, CMS’ Hospital Readmission Reduction Program began imposing financial penalties for excess readmissions among COPD patients and other common medical conditions . As a result of this financial incentive, hospitals across geographic regions have been implementing programmes directed at reducing readmissions among patients with COPD . Likely as a result of this, Medicare data has shown that readmission rates among COPD patients have declined markedly since 2012 .…”
Section: Discussionmentioning
confidence: 99%
“…; Hanes ; Krishnan et al. ). Some of these strategies, such as improved discharge planning, better care coordination, and enhanced patient education may be applied generally (noncondition‐specific) and scaled across condition categories with relative ease.…”
Section: Discussionmentioning
confidence: 99%
“…Despite best efforts, many readmissions may not be preventable. The US National COPD Readmissions Summit, as well as a recent systematic review, found that the evidence base to support specific interventions that would significantly reduce 30-day readmission rates in patients hospitalized for COPD exacerbations was inadequate 163,164…”
Section: Readmissionsmentioning
confidence: 99%